INFLUENCE OF GREEK MYTHOLOGY IN J.K. ROWLING’S "HARRY POTTER" (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article explores the significant influence of Greek mythology on J.K. Rowling's "Harry Potter" series, illustrating how mythological elements enhance character development and thematic depth. The author identifies various parallels between mythological figures and the characters in Harry Potter, such as the similarities between Harry and the hero archetype found in Greek mythology, particularly figures like Perseus. Furthermore, the article discusses the role of mythological creatures—like centaurs, which echo the centaurs of Greek lore, and the phoenix, reminiscent of the mythical bird from ancient myths. The author emphasizes how Rowling’s incorporation of these elements not only enriches the narrative but also connects modern readers to timeless themes of heroism, sacrifice, and morality inherent in Greek myths.